2023
DOI: 10.1186/s42155-023-00387-6
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion of thoracic duct stent resulting in recurrent chyluria: role of renal-lymphatic fistula embolization

Tran Quoc Hoa,
Nguyen Ngoc Cuong,
Le Hoan
et al.

Abstract: Background Thoracic duct (TD) stenting is considered a treatment option for certain pathological conditions caused by TD obstruction, such as chyluria. Several studies have reported on the efficacy of TD stent treatment for both obstructive and leakage condition of TD, but few have evaluated the stent patency. This report aims to describe the patency of TD stent and the effectiveness of renal-lymphatic fistula embolization in the treatment of chyluria. Case presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…13 Conversely, the recurrence of chyluria was observed when the stent became obstructed. 14 This study represents the largest cohort reported on the application of MRL and IL in patients with chyluria.…”
Section: Intranodal Lymphangiographymentioning
confidence: 97%
“…13 Conversely, the recurrence of chyluria was observed when the stent became obstructed. 14 This study represents the largest cohort reported on the application of MRL and IL in patients with chyluria.…”
Section: Intranodal Lymphangiographymentioning
confidence: 97%